2023
DOI: 10.1002/jmrs.654
|View full text |Cite
|
Sign up to set email alerts
|

Digital radiography reject analysis: A comparison between two radiology departments in New Zealand

Abstract: Introduction Image reject analysis (RA) in direct digital radiography (DDR) is an important quality indicator tool. Analysis of rejected images is a component of quality assurance (QA) programmes, with the overall aim of reducing patient radiation dose. This study aimed to compare differences in image rejection rates (RR) and the reasons for rejection between two radiology departments. Methods A retrospective quantitative descriptive study of images performed across the two radiology departments (RAD 1 and RAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…To a large extent, the exposure-related issues of film-screen technology have now been replaced with patient positioning errors. These findings are supported in this edition of Journal of Medical Radiation Sciences (JMRS), where Bantas et al 2 conducted a multisite study of digital radiography reject rates and reject rationales in 2021 in two New Zealand radiology departments. They reported that patient positioning was found to be the most common rationale for image rejection and calculated overall reject rates of 7.86% and 5.91% for each site.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…To a large extent, the exposure-related issues of film-screen technology have now been replaced with patient positioning errors. These findings are supported in this edition of Journal of Medical Radiation Sciences (JMRS), where Bantas et al 2 conducted a multisite study of digital radiography reject rates and reject rationales in 2021 in two New Zealand radiology departments. They reported that patient positioning was found to be the most common rationale for image rejection and calculated overall reject rates of 7.86% and 5.91% for each site.…”
mentioning
confidence: 73%
“…Despite these reject rates being considerably lower than reported rates for film‐screen departments which have been documented to be between 10% and 15%, 3,4 these findings further support the need for reject analysis in the digital age. Additionally, Bantas et al 2 . highlighted that it would be beneficial to include a review of radiographic positioning technique within the reject analysis process.…”
mentioning
confidence: 99%
“…In X-ray radiography, various factors can affect radiograph quality, such as positioning, exposure errors, and artifacts. [1][2][3] Low-quality radiographs can interfere with diagnoses, leading to image rejection and repeated exams. AAPM Report 151 indicates that 14% of patient exposure in projection radiography is due to repeated exams.…”
Section: Introductionmentioning
confidence: 99%
“…In X‐ray radiography, various factors can affect radiograph quality, such as positioning, exposure errors, and artifacts 1–3 . Low‐quality radiographs can interfere with diagnoses, leading to image rejection and repeated exams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation